1989
DOI: 10.1111/j.1440-1746.1989.tb00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between morphine responses and sphincter of Oddi motility in undefined biliary pain after cholecystectomy

Abstract: In 150 patients with undefined biliary pain after cholecystectomy, responses to morphine were compared with responses to morphine combined with neostigmine. The relationship between rises in plasma levels of aspartate aminotransferase (AST) after morphine or morphine-neostigmine and sphincter of Oddi motility as assessed by endoscopic manometry was also examined. When compared with morphine-neostigmine, patients given morphine alone showed a similar frequency (30% versus 33%) of increases in plasma levels of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…*P < 0.05. there were significant increases in groups 2, 3 and 5 (controls) at either 5 or 10min. When compared with values during infusion of the placebo, individual increases in plasma catecholamines after CCK-8 ranged from approximately 10 to 1400% and were largely restricted to early time points (5,lOmin). However, the amplitude of these changes was neither consistent among patients within each group nor predictive of scores for pain and nausea in individual patients.…”
Section: Time (Min)mentioning
confidence: 99%
See 1 more Smart Citation
“…*P < 0.05. there were significant increases in groups 2, 3 and 5 (controls) at either 5 or 10min. When compared with values during infusion of the placebo, individual increases in plasma catecholamines after CCK-8 ranged from approximately 10 to 1400% and were largely restricted to early time points (5,lOmin). However, the amplitude of these changes was neither consistent among patients within each group nor predictive of scores for pain and nausea in individual patients.…”
Section: Time (Min)mentioning
confidence: 99%
“…Significant increases in the ratio for noradrenaline were observed in groups 1,2 and 3 at 2 0 , s and lOmin respectively. For adrenaline and dopamine, Figure 2 Mean plasma concentrations of noradrenaline, adrenaline and dopamine before and after infusion of placebo in patients with pain and in control subjects (5). Patients with pain were divided into four groups; morphine responders with pain after cholecystectomy ( l ) , non-responders with pain after cholecystectomy (2), biliary pain (3) and irritable bowel syndrome (4).…”
Section: Time (Min)mentioning
confidence: 99%
“…In addition to its primary analgesic effects, this drug induces contraction of the sphincter of Oddi (5)(6)(7)(8)(9)(10)(11). The resultant obstruction to fluid outflow at the ampulla of Vater produces increased intraluminal pressure and, thereby, increased distention of the biliary and pancreatic ducts.…”
Section: Introductionmentioning
confidence: 97%
“…Rises in aminotransferase are more prominent than rises in other liver enzymes and appear to be the earliest marker of biliary obstruction.2 Rises in plasma amylase are rare after morphine alone and appear to be less useful than aminotransferase as a marker of altered responsiveness to the combination of morphine and neostigmine.2 4 Results from the present study showed that morphine induced significant rises in plasma concentrations of noradrenaline and dopamine in patients showing rises in plasma concentrations of aminotransferase. For noradrenaline, significant rises were noted at 40 and 60 minutes after morphine, times which often preceded and closely followed the onset of pain.…”
Section: Discussionmentioning
confidence: 57%